PENGARUH LITERASI ASURANSI, RELIGIUSITAS, DAN KUALITAS PELAYANAN TERHADAP MINAT GENERASI MILENIAL MENGGUNAKAN ASURANSI SYARIAH - Rama Muhamad Pramudya, (2021)
In every person's life, of course, it cannot be separated from a risk that can't be predicted when it occur, that risk can cause a loss therefore, self-protection is an action that helps and minimizes the losses caused by these risks. Attention to the millennial generation who are considered to still do not care about insurance and tend to be more concerned with lifestyle than self-protection by having insurance. Therefore, This study aims to analyze the effect of insurance literacy, religiosity and service quality on the millennial generation interest in using sharia insurance. The research method used in this study is quantitative collecting data using primary data taken through the distribution of questionnaires and using purposive sampling method, with a total sample of 148 respondents. Data analysis techniques were tested through regression analysis with analytical test tools, namely statistical product and service solutions (SPSS). The findings of this study indicate that the variables of insurance literacy, religiosity and service quality have a significant effect on the millennial generation's interest in using sharia insurance.Furthermore, partially found in this study that the religiosity variable has no effect and is not significant on the millennial generation's interest in using sharia insurance. The contribution in this study is to provide an overview of understanding insurance literacy, religiosity and views on service quality in the sharia insurance industry in increasing its market.